The effect of imageability and predicability of cues in autobiographical memory. - Williams, J; Healy, H; Ellis, N (1999)
Four experiments investigated the role of imagery in the recollection of autobiographical memories. The first two experiments examined the effects of word imageability and word frequency on the retrieval of personal memories in a cued autobiographical memory task. They showed that the imageability of cues (but not frequency) mediates specificity in the recall of personal memories. Experiment 2 explored how different imagery modalities (visual, olfactory, tactile, auditory, and motor) influence autobiographical retrieval. Consistent with research on imagery modalities in verbal learning paradigms, visual imageability emerged as the most significant predictor of specificity. Experiments 3 and 4 examined how far a knowledge-based account of imagery effects might account for these effects, using predicability as a measure of semantic richness of a cue. Results found that visual imageability of cues accounted for more variance in specificity of recall than did predicability. The results are explained in terms of the way images represent the most efficient form of summarizing the information that can be used at each stage of the recollection process: setting the retrieval plan, strategic search, and evaluation of candidate episodes.